2019
DOI: 10.1038/s41385-018-0107-3
|View full text |Cite
|
Sign up to set email alerts
|

Selective expression of constitutively activated STAT6 in intestinal epithelial cells promotes differentiation of secretory cells and protection against helminths

Abstract: Intestinal epithelial cells (IECs) constitute an important barrier between host and pathogen. Immune mechanisms that provide protection against gastrointestinal helminths often require IL-4Rα-induced activation of STAT6-regulated genes in IECs. However, it is not known whether STAT6 activation in IECs enhances protective immunity against helminths. Furthermore, the regulation of proliferation and differentiation processes of the intestinal epithelium by IEC-intrinsic STAT6 signaling remains unclear. To address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…This is consistent with reduced IL-22 signaling (75) and altered goblet cell development (79)). In addition, STAT6, a key regulator of secretory lineage differentiation, was predicted to have lower activity in OLFM4 expressing stem cells and immature enterocytes (80). This is consistent with predicted upregulation of MYC in secretory precursors and goblet cells, which negatively regulates differentiation towards goblet cells (81).…”
Section: Us Cohortssupporting
confidence: 71%
“…This is consistent with reduced IL-22 signaling (75) and altered goblet cell development (79)). In addition, STAT6, a key regulator of secretory lineage differentiation, was predicted to have lower activity in OLFM4 expressing stem cells and immature enterocytes (80). This is consistent with predicted upregulation of MYC in secretory precursors and goblet cells, which negatively regulates differentiation towards goblet cells (81).…”
Section: Us Cohortssupporting
confidence: 71%
“…Gastrointestinal helminth infection represents one of the most widespread chronic human parasitoses and several mouse models serve as well‐established tools to study helminth‐induced type 2 immune responses and cytokine regulation . Mice infected with the rodent nematode Nippostrongylus brasiliensis ( Nb ) have revealed that the protective anti‐helminth immunity is largely dependent on IL‐4/IL‐13‐induced STAT6 activation . Using T cell‐specific IL‐4/IL‐13‐deficient mice (4‐13Tko), we previously showed that IL‐4/IL‐13 produced by cells of the innate immune system is required for effective type 2 immune responses against Nb .…”
Section: Introductionmentioning
confidence: 99%
“…We do not know the specific time for the pathological transformation of the IL-4/STAT6 signaling pathway favoring CAC development such that it is detrimental to the immune response. In fact, during steady-state conditions, IL4R downstream transcription factor STAT6 promotes the proliferation and differentiation of secretory intestinal epithelial cells (IECs) in normal colon tissue [ 56 ]. Not only that, STAT6 overactivation in IECs has been associated with loss of the tight junctions that leads to permeability dysregulation, bacterial translocation and changes in the microbiome, as well as intestinal inflammation and tumorigenesis [ 57 ].…”
Section: Discussionmentioning
confidence: 99%